PSXV-19 Fetal Blood Oxygenation and Placental Efficiency Is Increased By Melatonin Implants in Sheep. (7th December 2018) - Sales, F; Parraguez, V; McCoard, S; Cofré, E; Peralta, O; Subiabre, I; González-Bulnes, A
Abstract: In sheep, maternal melatonin implants from day 100–140 of gestation increases fetal weight. In rats, melatonin supplementation increases fetal weight via improved placental efficiency and reduction of oxidative stress. However, it is not clear if same mechanisms are involved in sheep. Our aim was to evaluate whether increased fetal weight associated with melatonin supplementation (Regulin®) at day 100 of pregnancy (P100), influence fetal hypoxia and placental efficiency at P140 in single (S)- or twin-bearing (T) ewes, with either 0 (0MEL), 1 (1MEL) or 2 (2MEL) 18-mg melatonin implants (n=8 per group). At P140, partial pressure of oxygen (PO2) and oxygen saturation of hemoglobin (Sat-O2) were measured in fetal umbilical vein blood samples. Each placenta per fetus was excised and placentomes weighed and typed (A-D). Birth rank, number of implants and their interaction on blood gases, placentome weight and placental efficiency (fetal:placental weight ratio and changes in placentome type) were analyzed using ANOVA. Association between PO2, Sat-O2 and fetal weight was established using Pearson correlation. The 5–8% increase in body weight of 2MEL fetuses was associated with an 18–20% increase in umbilical blood PO2 (P<0.05) compared to 1MEL and 0MEL fetuses, respectively. Fetal weight was positively correlated with PO2 (r=0.37, P=0.02) and Sat-O2 (r=0.26, P=0.03). No treatment effect on placentome average weight, total placentome weight per fetus or per ewe nor total number of placentomes per fetus was observed. However, 2MEL had higher Type C (P<0.05) than 0MEL and 1MEL ewes, and tended to have lower proportion of Type A (P=0.1), and higher proportion of Type D (P=0.06) placentomes, compared to 0MEL ewes. Placental efficiency tended (P<0.1) to be higher in T-1MEL than all other groups. These results suggest that melatonin-induced increased fetal weight is associated with improved fetal oxygen supply and adaptations to improve placental efficiency. *Funded by FONDECYT 11150998.